Dissecting the Biology of Menstrual Cycle-Associated Breast Cancer Risk - Atashgaran, Vahid; Wrin, Joseph; Barry, Simon Charles; Dasari, Pallave; Ingman, Wendy V. (Frontiers in Oncology, 2016)
Fluctuations in circulating estrogen and progesterone across the menstrual cycle lead to increased breast cancer susceptibility in women; however the biological basis for this increased risk is not well understood. Estrogen and progesterone have important roles in normal mammary gland development, where they direct dynamic interactions among the hormonally-regulated mammary epithelial, stromal, and immune cell compartments. The continuous fluctuations of estrogen and progesterone over a woman’s reproductive lifetime affects the turnover of mammary epithelium and stem cells, as well as regulating the phenotype and function of the mammary stromal and immune cells such as macrophages, regulatory T cells and the extracellular matrix. Collectively, these events may result in genomic instability, increase the chance of random genetic mutations, dampen immune surveillance, and promote tolerance in the mammary gland, and thereby increase the risk of breast cancer initiation. This article reviews the current status of our understanding of the molecular and the cellular changes that occur in the mammary gland across the menstrual cycle, and how continuous menstrual cycling may increase breast cancer susceptibility in women.